Penyebaran Iklan pada Media Elektronik yang Memuat Konten Pornografi - Ratu Agung Dewangga Arinatha Gunawan; I Nyoman Gede Sugiartha; Ni Made Sukaryati Karma (Fakultas Hukum, Universitas Warmadewa, 2021)
The government has issued Law Number 44 of 2008 concerning pornography. The objectives of this law are, among other things, to maintain and realize social life that is ethical, has a noble personality, upholds the values ​​of the One and Only Godhead, and respects the dignity and dignity of humanity. The purpose of research on legal regulations regarding pornographic advertisements on social media and as well as efforts to prevent perpetrators of spreading advertisements on electronic media containing pornographic content. The type of research used is normative legal research with a statutory approach and a conceptual approach. Sources of legal materials used are divided into primary, secondary and tertiary legal materials. The technique of collecting material in research uses library research techniques, namely reading, taking notes, quoting, summarizing, and examining data information from regulations or literature related to the problem. Furthermore, the data collected was analyzed using a systematic method of handling legal materials.